Frequency of Polycystic Ovaries as a Causative Factor in Primary Infertility of Patients Undergoing Laparoscopy in Lady Reading Hospital - Habib, Amna; Khattak, Saima; Khan, Hafsa; Ume Kulsoo; Habib, Fatima (Indus Journal of Bioscience Research, 2025)
Background: Polycystic ovary is commonly seen in primary infertile women and tends to impact diagnostic as well as management plans considerably. Laparoscopy continues to be helpful in confirming it, but its association with several demographic as well as clinical parameters needs to be studied further in local populations. Objective: To determine the frequency of polycystic ovaries in patients with primary infertility undergoing laparoscopy in Lady Reading Hospital Peshawar. Study Design: Cross-sectional study. Duration and Place of Study: April 2024 to September 2024, Department of Obstetrics and Gynaecology, Lady Reading Hospital, Peshawar. Methodology: A total of 143 married women aged 18–45 years, unable to conceive despite ≥12 months of regular unprotected intercourse, and scheduled for diagnostic laparoscopy, were included through consecutive sampling. Women with prior laparoscopic procedures, endocrine disorders, or liver disease were excluded. Demographic and clinical details were recorded, and laparoscopy was performed under general anesthesia. Polycystic ovaries were diagnosed when three or more characteristic features—enlarged ovarian volume, smooth and tense surface with prominent vascularity, multiple subcapsular cysts, or cysts with clear/yellow fluid—were present. Results: The mean age was 29.92±6.10 years, with a mean infertility duration of 5.01±3.21 years. Polycystic ovary was present in 28% of participants. Significant associations were observed with age (p